Assessing catchment scale flood resilience of urban areas using a grid cell based metric. (15th October 2019) - Wang, Yuntao; Meng, Fanlin; Liu, Haixing; Zhang, Chi; Fu, Guangtao
Abstract: Urban flooding has become a global issue due to climate change, urbanization and limitation in the capacity of urban drainage infrastructures. To tackle the growing threats, it is crucial to understand urban surface flood resilience, i.e., how urban drainage catchments can resist against and recover from flooding. This study proposes a grid cell based resilience metric to assess urban surface flood resilience at the urban drainage catchment scale. The new metric is defined as the ratio of the number of unflooded grid cells to the total grid cell number in an urban drainage catchment. A two-dimensional Cellular Automata based model CADDIES is used to simulate urban surface flooding. This methodology is demonstrated using a case study in Dalian, China, which is divided into 31 urban drainage catchments for flood resilience analysis. Results show the high resolution resilience assessment identifies vulnerable catchments and helps develop effective adaptation strategies to enhance urban surface flood resilience. Comparison of the new metric with an existing metric reveals that new metric has the advantage of fully reflecting the changing process of system performance. Effectiveness of adaptation strategies for enhancing urban surface flood resilience is discussed for different catchments. This study provides a new way to characterize urban flood resilience and an in-depth understanding of flood resilience for urban drainage catchments of different characteristics, and thus help develop effective intervention strategies for sustainable sponge city development. Graphical abstract: Image 1 Highlights: A new grid cell based resilience metric reveals flood dynamics of urban catchments. The metric shows different resilience performances not captured by simplified ones. Upstream and downstream adaptation strategies can effectively enhance resilience. Resilience analysis is useful for urban flood management in building sponge cities.